Nuevas localidades para peces de agua dulce de la Argentina IV : Adiciones a la ictiofauna del río Uruguay y algunos afluentes - López, Hugo Luis (1984)
From 58 species collected in the Uruguay river and some of its affluents, new localities are reported for six Characoidei species (Schizodon ptatae, Glandulocauda terofali, Holoshestes pcquira, Hyphessobrycon luetkeni, H. meridionatis and Aphyocharax rubropinnis) and for three Siluriformcs (Megalodoras iaevigatulus, Auchenipterus nuchalis and Bunocephalus ihe- ringi). For these nine species morphological data and complete Argentine references arc given. Chemical data on the affluents are checked with those from neighbouring areas.